using world health organisation near miss approach to assess preventable maternal morbidity and mortality at a tertiary care hospital - Asma Ansari; umbreen akram; samina khattak (Journal of the Pakistan Medical Association, 2021)
Objectives: To determine frequency of severe maternal complications, maternal near-miss cases and maternal deaths in obstetric patients at a tertiary care hospital using WHO near miss approach. Study Design: Cross-sectional analytical study Place and duration of study: This was conducted at obstetrics unit of CMH Kharian from Jan 2019 – June 2019 Methodology: Inclusion criteria for baseline assessment was near miss approach which comprises of severe maternal complications, critical interventions and life threatening conditions using WHO near miss approach 2009 for case identification. Demographic and reproductive profiles including age, parity, period of gestation, booking status, mode of delivery were calculated. Women with life threatening conditions including near miss and maternal mortality cases were calculated. Severe maternal outcome ratio, maternal near miss and maternal mortality ratio, mortality to near miss ratio and mortality index was calculated. Results: There were 1054 live births. Out of which 42 were near miss cases and 04 maternal deaths. Management based criteria identified 34(80%) followed by clinical 14(33%) and laboratory criteria 02(4.7%) respectively. Maternal mortality ratio was 379/100,000 and NMMR was 39 /1000 live births. Severe maternal outcome ratio was 43.6%.For near miss cases mortality index was 8.6.MNM:MD ratio was 10.5:1. Conclusion: The study concludes that a standardized near miss criterion makes audit and comparison of results in between hospitals and even countries having the same resources possible and reproducible. Particular advantage is its uniform approach which when correctly applied produces Continuous...